Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd008873.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation for women during pregnancy

Abstract: BACKGROUND: Vitamin D deficiency or insufficiency is thought to be common among pregnant women. Vitamin D supplementation during pregnancy has been suggested as an intervention to protect against adverse pregnancy outcomes. OBJECTIVES: To examine whether oral supplements with vitamin D alone or in combination with calcium or other vitamins and minerals given to women during pregnancy can safely improve maternal and neonatal outcomes. METHODS:Search methods: We searched the Cochrane Pregnancy and Childbirth Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
178
1
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(203 citation statements)
references
References 128 publications
(172 reference statements)
9
178
1
15
Order By: Relevance
“…In contrast, Cadario et al [35] reported that all mothers supplemented with vitamin D (who used daily a standard prenatal multivitamin containing 400 IU of vitamin D) demonstrated higher 25(OH)D 3 values in neonatal serum. Similarly, a systematic review during pregnancy showed that with supplementation there is an increase of serum 25(OH)D 3 levels in neonates [36]. …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Cadario et al [35] reported that all mothers supplemented with vitamin D (who used daily a standard prenatal multivitamin containing 400 IU of vitamin D) demonstrated higher 25(OH)D 3 values in neonatal serum. Similarly, a systematic review during pregnancy showed that with supplementation there is an increase of serum 25(OH)D 3 levels in neonates [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Maternal vitamin D deficiency, especially in early pregnancy, has been associated with risk of preeclampsia, preterm birth and small-for-gestational-age (SGA) infants [52,53]. A systematic review of vitamin D in pregnancy showed an overall reduction in LBW of borderline significance [53]. …”
Section: Maternal Micronutrient Deficiency: Burden Significance and mentioning
confidence: 99%
“…Measuring VD insufficiency in pregnant women is complicated by a lack of agreement in some aspects, such as the accuracy of 25(OH)D levels as marker of deficiency, normal VD levels in pregnancy, and the identification of gold standard test for VD deficiency [14]. 25(OH)D is the clinical and research gold standard measure of VD status [15].…”
Section: Identifying Vitamin D Deficiencymentioning
confidence: 99%
“…For that reason, the clinical significance of vitamin D supplementation as a part of routine antenatal care must be considered. Supplementation studies conducted with recommended daily allowance of 400 IU have not shown any improvement in vitamin D status of pregnant women [14]. Higher doses given as a daily dose of 800 IU or bolus dose of 200,000 IU given as a single dose or 2/3 divided doses given once a month have shown significant improvement [14].…”
Section: Treating Vitamin D Deficiency In Pregnancymentioning
confidence: 99%